2019
DOI: 10.21276/ijcmsr.2019.4.3.17
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Kidney Length in Estimation of Gestation Age by Sonography

Abstract: Various biometric parameters like BPD, HC, AC and FL are used either independently or as an average of all the parameters in estimation of fetal gestation. This study evaluates estimation of gestational age by fetal renal length as correlated with other standard biometric parameters. Material and Methods: This was a single institutional prospective cross-sectional study which included healthy pregnant females with known LMP and dating scan between 26 weeks to 40 weeks of gestation. 100 consecutive pregnant wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Kaul I et al [6] also advocated that the single most accurate parameter for estimating GA is the FKL. Kiran L et al [11] in their study determined that FKL correlated well with GA estimated from standard fetal biometry and can be used as an independent parameter in estimation of fetal GA. Das SK et al [12] concluded that FKL showed a strong correlation with GA compared to other conventional parameters and can easily be included in routine obstetric scan to enhance the accuracy of GA measurement and in cases where conventional parameters are difficult to obtain.…”
Section: Discussionmentioning
confidence: 94%
“…Kaul I et al [6] also advocated that the single most accurate parameter for estimating GA is the FKL. Kiran L et al [11] in their study determined that FKL correlated well with GA estimated from standard fetal biometry and can be used as an independent parameter in estimation of fetal GA. Das SK et al [12] concluded that FKL showed a strong correlation with GA compared to other conventional parameters and can easily be included in routine obstetric scan to enhance the accuracy of GA measurement and in cases where conventional parameters are difficult to obtain.…”
Section: Discussionmentioning
confidence: 94%